Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Kantor Dinas Pariwisata, Kepemudaan Dan Olahraga Kabupaten Barru - Hartati, Hartati; Ade Irwan, Andi Indah Anggerwati, Nirwan, Sulaik Abdul Hamid, (Pascasarjana STIE Amkop Makassar, 2024)
The purpose of this study is to find out the organizational culture and job satisfaction on the performance of civil servants at the Barru Regency Tourism, Youth and Sports Office have a partial and simultaneous effect. This research was conducted using qualitative and quantitative methods. The data collection technique used was a primary data collection technique sourced from the answers of 38 respondents. The tests used include Validation Test, Reliability Test, Multiple Linear Regression Analysis, and t Test (partial), F Test (simultaneous), R2 Test (determination coefficient). The results of this study show that the Organizational Culture Variable is obtained tcount = 3.028 > ttable 2.030 and a significant value of 0.005 < 0.05. With a significant value equal to 0.05, it shows that organizational culture (X1) has a positive and significant influence on employee performance. Meanwhile, the results of the job satisfaction variable are obtained tcount = 3.769 > ttable = 2.030 and a significant value of 0.001 < 0.05. With a significant value below 0.05, it shows that job satisfaction (X2) has a positive and significant influence on employee performance.Keywords: Organizational Culture, Job Satisfaction, Employee Performance.